FNC: An Advanced Anticancer Therapeutic or Just an Underdog? - Fayzullina, Daria; Kharwar, Rajesh Kumar; Acharya, Arbind; Buzdin, Anton; Borisov, Nicolas; Timashev, Peter; Ulasov, Ilya; Kapomba, Byron (Frontiers in Oncology, 2022)
Azvudine (FNC) is a novel cytidine analogue that has both antiviral and anticancer activities. This minireview focuses on its underlying molecular mechanisms of suppressing viral life cycle and cancer cell growth and discusses applications of this nucleoside drug for advanced therapy of tumors and malignant blood diseases. FNC inhibits positive-stand RNA viruses, like HCV, EV, SARS-COV-2, HBV, and retroviruses, including HIV, by suppressing their RNA-dependent polymerase enzymes. It may also inhibit such enzyme (reverse transcriptase) in the human retrotransposons, including human endogenous retroviruses (HERVs). As the activation of retrotransposons can be the major factor of ongoing cancer genome instability and consequently higher aggressiveness of tumors, FNC has a potential to increase the efficacy of multiple anticancer therapies. Furthermore, FNC also showed other aspects of anticancer activity by inhibiting adhesion, migration, invasion, and proliferation of malignant cells. It was also reported to be involved in cell cycle arrest and apoptosis, thereby inhibiting the progression of cancer through different pathways. To the date, the grounds of FNC effects on cancer cells are not fully understood and hence additional studies are needed for better understanding molecular mechanisms of its anticancer activities to support its medical use in oncology.